Jewels - Steel, Danielle (New York, N.Y. : Delacorte Press, 1992)
Birthdays are a time for reflection, especially for Sarah, Duchess of Whitfield, who is awaiting the arrival of her far-flung family. Years earlier, reeling from her pending divorce, Sarah Thompson is force-marched through Europe on the grand tour by her concerned parents. Disinterested in the sons, grandsons, and nephews paraded before her by well-meaning acquaintances, Sarah chances upon William Whitfield, the Duke of Whitfield, 14th in line for succession to the English throne. Disarmed by his wit and intrigued by his intellect, Sarah allows William to become her companion in London, warning him they can only be friends. Undeterred, William dismisses Sarah's protestations that her divorce makes her unsuitable to be his duchess and finally convinces Sarah to marry him. While honeymooning in France, Sarah and William happen upon Chateau de la Meuze. Enchanted, the Whitfields buy and set about restoring the estate. But World War II looms, threatening their idyllic existence. Following the birth of their first child, Phillip, William joins the RAF when England declares war on Germany. Reluctantly, he leaves Sarah and Phillip at the chateau. German troops, led by the courtly commandant Joachim von Mannheim, take possession of the chateau to establish a hospital, removing Sarah and Phillip to the caretaker's cottage. When the war ends, William, after being imprisoned for three years and barely surviving the torture that deprived him of the use of his legs, returns to his family. The Whitfields pick up threads of lives strained, but not broken, by war. Soon, they are approached by others who lost everything during the war except a few secreted heirlooms. But jewelry can't put food on the table, and the Whitfields begin purchasing jewelry to provide neighbors with much-needed cash. When William jokingly suggests opening a Paris store, a legacy is born: Whitfield's, Jewelers to the Crown.
Keywords: Family-owned business enterprises -- Fiction; World War, 1939-1945 -- France -- Fiction; Parent and adult child -- Fiction; Americans -- France -- fiction; British -- France -- Fiction; Jewelry trade -- Fiction; France -- Fiction